Autologous Hematopoietic Cell Transplantation in Multiple Sclerosis: Changing Paradigms in the Era of Novel Agents - Maria Gavriilaki; Ioanna Sakellari; Eleni Gavriilaki; Vasilios K. Kimiskidis; Achilles Anagnostopoulos (Hindawi Limited, 2019)
Autologous hematopoietic stem cell transplantation (AHSCT) is established as a standard of care for diseases ranging from hematological malignancies to other neoplastic pathologies and severe immunological deficiencies. In April 1995, our group performed the first AHSCT in progressive multiple sclerosis (MS). Since then, a plethora of studies have been published with encouraging but controversial results. Major challenges in the field include appropriate patient selection, improvements in AHSCT procedure, and timing of this treatment modality. Beyond AHSCT, several new intravenous or oral agents have been developed and approved over the last 20 years in MS. The emergence of multiple effective therapies for MS has created a challenging scenario for both treating physicians and patients. Novel cell-based therapies other than AHSCT are also currently investigated in MS patients with promising results. Our review is aimed at summarizing state-of-the-art knowledge on basic principles and results of AHSCT in MS and its role compared to novel agents.